Konsep, Teori Pengembangan dan Implementasi Manajemen Pendidikan Islam di Pondok Pesantren Banyuanyar Putri - faizatul; Mar’atus , Shalihah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Darul Ulum Banyuanyar Putri Islamic Boarding School in managing education effectively integrates religious teachings with management theory and practice to achieve optimal educational goals. In the era of globalization and the development of information technology, demands on the management of Islamic boarding school educational institutions are increasingly complex, so that a deep understanding of the concept, development theory, and its implementation is needed so that Islamic boarding schools can adapt and develop sustainably. This study aims to examine how Islamic education management is applied in Islamic boarding school management, starting from planning, organizing, implementing, and evaluating. The method used is a qualitative study with a descriptive approach through observation and interviews. The results of the study show that the implementation of Islamic education management in this Islamic boarding school integrates Islamic values ​​in an effective and efficient management system, by adjusting management theory and local wisdom of the Islamic boarding school.